FREQUENCIES AND FUNCTIONS OF REPORTING VERBS USED IN TESOL RESEARCH ARTICLES BY VIETNAMESE WRITERS - Thi Kim Loan, Bui (VNU Journal of Foreign Studies; Vol 38 No 3DO - 10.25073/2525-2445/vnufs.4843, 2022)
How to ensure proper reporting verbs (RVs) to be used in academic writing remains a difficulty to Vietnamese research writers. Nguyen and Pramoolsook’s (2015) study findings reveal that Vietnamese TESOL students inappropriately use RVs in their master’s theses in terms of function, voice and tenses. This corpus-based study aimed to investigate the frequencies and functions of RVs in TESOL research articles written by Vietnamese writers based on RMIT University Study and Learning Center’s (2012) categorization of RVs in terms of position or evaluation. The corpus consisted of 35 TESOL research articles collected from a PDF book of TESOL international conference proceedings. The data were processed using Microsoft Word and Microsoft Excel. The findings revealed that TESOL research Vietnamese writers had a tendency to use groups of RVs with neutral position or evaluation. The results of the functional analysis of RVS indicated eleven functions of RVs including agreement, argument/persuasion, believing, conclusion, disagreement/questioning, discussion, emphasis, evaluation/examination, explanation, presentation, and discussion. The results provide TESOL research Vietnamese writers, research scholars as well as students from all disciplines at higher education with more knowledge of RVs that they can use for their future academic writing and international publishing.